A case of hereditary coproporphyria with posterior reversible encephalopathy and novel coproporphyrinogen oxidase gene mutation c.863T>G (p.Leu288Trp). (September 2018) - Lambie, Deborah; Florkowski, Chris; Sies, Chris; Raizis, Anthony; Siu, Wai-Kwan; Towns, Cindy
A 21-year-old female had recurrent presentations to the emergency department with myalgia, vomiting, abdominal pain and subsequently developed generalized seizures. She was volume depleted with a plasma sodium of 125 mmol/L (reference interval: 135–145) and she had fluctuating hypertension. Acute porphyria was suspected and confirmed with raised urine porphobilinogen/creatinine ratio of 12:4 μmol/mmoL (reference interval < 1:5) and she was treated with intravenous haem arginate. Urinary porphyrin/creatinine ratio was 673 nmol/mmoL (reference interval <35) and faecal porphyrins 2430 μmol/kg dry weight (reference interval: <200) were markedly elevated, with raised faecal CIII:CI ratio, consistent with acute coproporphyria. Diagnosis was confirmed by the demonstration of a novel missense variant in the coproporphyrinogen oxidase gene c.863T > G (p.Leu288Trp) predicted to be deleterious and which segregated with three other affected family members. Although CT head was normal, magnetic resonance imaging scan revealed symmetrical signal abnormalities and swelling in the parietal and occipital lobes consistent with posterior reversible encephalopathy. Over several days, her seizures ceased and sodium and blood pressure normalized. The aetiology of the acute porphyric attack was likely multifactorial with contributions from a recent viral illness and caloric deprivation. No drug precipitant was identified. We postulate that untreated hypertension played a key role in the development of posterior reversible encephalopathy. Early clinical suspicion and urine porphobilinogen testing are the key components in preventing morbidity and mortality in acute porphyrias.